VD_FINDINFO Arrêt / 2011 / 1211 vom 27. September 2011 - VD Tribunal cantonal (2011)
INTERDICTION, PROPORTIONNALITÉ, EXPERTISE, DÉCISION D'IRRECEVABILITÉ | 369 CC, 370 CC, 393 CPC, 396 al. 3 CPC, 398d al. 2 CPC, 91 let. c CPC, 92 al. 1 CPC